2009
DOI: 10.1590/s0100-83582009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Períodos de interferência de plantas daninhas na cultura do sorgo forrageiro em terras baixas

Abstract: RESUMO -Objetivou-se com este trabalho avaliar a eficiência do método mecânico de controle de plantas daninhas na cultura do sorgo e determinar o período crítico de competição da cultura com a comunidade infestante em terras baixas de clima temperado, considerando o estádio de desenvolvimento das plantas de sorgo. O experimento foi instalado em condições de campo, em Planossolo hidromórfico cultivado nos últimos cinco anos com arroz, com população elevada de plantas daninhas, principalmente capim-arroz (Echino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
1
7
0
5
Order By: Relevance
“…According to Andres et al (2009), under temperate conditions and in lowlands, the optimal period for weed control in forage sorghum crops is between the emergence of the third and seventh leaf of the plant. On the other hand, Cabral et al (2013) conducted a research with grain sorghum in Goiás State and found that the optimum period to perform the control is between the emergence of the fifth and ninth leaf.…”
Section: Resultsmentioning
confidence: 99%
“…According to Andres et al (2009), under temperate conditions and in lowlands, the optimal period for weed control in forage sorghum crops is between the emergence of the third and seventh leaf of the plant. On the other hand, Cabral et al (2013) conducted a research with grain sorghum in Goiás State and found that the optimum period to perform the control is between the emergence of the fifth and ninth leaf.…”
Section: Resultsmentioning
confidence: 99%
“…Verificou-se, ainda, que o final deste período é o momento adequado para o controle, pois as plantas daninhas se encontram no início do desenvolvimento, apresentando baixa densidade de indivíduos e acúmulo de massa seca, quando as técnicas de controle empregadas são geralmente mais eficientes. Andres et al (2009), em pesquisa realizada com a cultura do sorgo cultivado em terras baixas, em clima temperado, verificaram que o período adequado para realizar o controle de plantas daninhas situa-se entre a emissão da terceira e da sétima folha da planta.…”
Section: Resultsunclassified
“…However, plants which had already established after this period, are still capable of promoting a significant reduction in the crop yield, which normally do not occurs in crops that are higher sized, such as the sunflower (BRIGHENTI et al, 2004), soybean (MESCHEDE et al, 2004) and sorghum (ANDRES et al, 2009).…”
Section: Resultsmentioning
confidence: 99%